2019
DOI: 10.1016/j.abb.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and preliminary characterisation of the cytochrome P450 monooxygenases from Frankia sp. EuI1c (Frankia inefficax sp.)

Abstract: Analysis and preliminary characterisation of the cytochrome P450 monooxygenases from Frankia sp. EuI1c (Frankia inefficax sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…P450s, ferredoxins, and smBGCs data for Firmicutes species were retrieved from published articles [30,31] and used for comparative analysis. Ferredoxins proteins used for data mining were retrieved from published articles [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Comparative Analysis Of P450s Ferredoxins and Smbgcs Datamentioning
confidence: 99%
“…P450s, ferredoxins, and smBGCs data for Firmicutes species were retrieved from published articles [30,31] and used for comparative analysis. Ferredoxins proteins used for data mining were retrieved from published articles [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Comparative Analysis Of P450s Ferredoxins and Smbgcs Datamentioning
confidence: 99%
“…It is rare for a proline residue to directly follow the acid–alcohol pair. , For example, none of the 57 human CYPs or the 68 or 47 bacterial CYPs from Frankia inefficax sp. or Mycobacterium marinum, respectively, have a proline at this position. , These differences result in the glutamate residue (E249) in GcoA having a different conformation and being held further from the heme (8.1 Å, PDB code: 5NCB) than the glutamate in the CYP199A4 T252E mutant (4.2 Å, PDB code: 7REH; Figure ). Our hypothesis is that we should be able to improve the peroxygenase activity of CYP199A4 over that of the single T252E mutant by modifying the nearby residues of the I-helix.…”
Section: Introductionmentioning
confidence: 99%
“…There is also an unusual proline and glycine pair of residues immediately after the glutamate residue in the amino acid sequence of GcoA (Figures and S1). It is rare for a proline residue to directly follow the acid–alcohol pair. , For example, none of the 57 human CYPs or the 68 or 47 bacterial CYPs from Frankia inefficax sp. or Mycobacterium marinum, respectively, have a proline at this position. , These differences result in the glutamate residue (E249) in GcoA having a different conformation and being held further from the heme (8.1 Å, PDB code: 5NCB) than the glutamate in the CYP199A4 T252E mutant (4.2 Å, PDB code: 7REH; Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been limited studies on the bacterial CYPs (Parvez et al 2016;Mthetwa et al 2018;Senate et al 2019;Lau et al 2019;Khumalo et al 2020) compared to eukaryotes (Parvez et al 2016). Nevertheless, observations on the role of CYPs in bacterial pathogenesis (Kweon et al 2020), use of CYP141 for diagnosis of Mycobacterium tuberculosis (Darban-Sarokhalil et al 2011) and indispensability of CYP121 for the existence of tuberculosis pathogen (McLean et al 2008) demonstrated its importance in infectious bacteria.…”
Section: Introductionmentioning
confidence: 99%